We cannot wish for success, and we cannot seek it. Success is not the goal. It is the result of our work. - Pahor, Dušica (Acta Medico-Biotechnica, 2024)
The Day of the University of Maribor, September 12, 2024 - Upon the presentation of this year's awards and acknowledgments on the Day of the University of Maribor, I was given the pleasant opportunity to show my gratitude on behalf of all award winners. Among this year's recipients was Sir Gregory Paul Winter, who won the Nobel Prize in chemistry in 2018, and who on that auspicious day was awarded an honorary doctorate by the university ...